Awareness of Salt Intake among Community-Dwelling Elderly at Coastal Area: The Role of Public Health Access Program - Farapti Farapti; Aprilia Devi Fatimah; Erni Astutik; Atik Choirul Hidajah; Thinni Nurul Rochmah (Journal of Nutrition and Metabolism)
A geographical location such as coastal area is known as risk factor hypertension relating to high exposure of salty foods. Public health access had significant effect on reducing salt intake at the community level. This study assesses salt intake in older women resident at urban coastal in Indonesia participating in the public health program. This was a cross-sectional study involving older women (56.98 ± 5.7 years) resident at urban coastal in Kenjeran, Surabaya, Indonesia. Salt intake was calculated and estimated based on 24-h urinary sodium. The mean daily salt intake was 6.16 ± 3.48 g/d; only 11.8% of subjects consumed salt intake <3 g/day. However, majority of subjects (62.8%) consume salt <6 g/d. Awareness and participation were associated significantly with low salt intake. A significant association between participation, awareness, and salt intake may suggest that participating regularly in the public health program might cause our subjects controlled excessive salt intake by limiting their salt consumption. Since daily salt intake is still significant high and hypertension is still prevalence, comprehensive strategies to reduce salt should be considered in development of sodium-reduction initiatives in this region.